THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND SPIRITUAL NEEDS WITH THE LEVEL OF ANXIETY OF PREOPERATIVE PATIENTS IN THE OPERATING ROOM OF RSUD PARIAMAN - ANDRIANI, LINDA; ARINI, LARASUCI; AMELIATI, SRI (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2025)
Preoperative is the period before surgery which often causes anxiety in patients. Anxiety can arise as a response to situations that are considered dangerous or threatening such as symptoms of shortness of breath, rapid heartbeat and dizziness. The family plays a very important role in providing support to patients so that it can reduce anxiety. This anxiety can also be reduced by fulfilling spiritual needs. This study aims to determine the relationship between family support and spiritual needs with the level of anxiety of preoperative patients in the operating room of Pariaman Hospital. This study uses a quantitative method with a cross-sectional design. The study was conducted in the operating room of Pariaman Hospital on July 3-16, 2024. The study population was patients and their families and patients who were in the operating room of Pariaman Hospital. The study sample consisted of 43 people selected using the accidental sampling technique. The research instrument was a questionnaire. Data analysis was carried out using Chi Square at the α level = 5%. The results showed that most respondents had low family support, namely 24 people (55.8%) and lacking spiritual needs, namely 22 people (51.2%). The most common level of anxiety found was mild anxiety, which was 25 people (58.1%). There was a significant relationship between family support and anxiety levels (p-value = 0.001 <α = 0.05) and there was also a significant relationship between spiritual needs and anxiety levels (p-value = 0.002 <α = 0.05) of preoperative patients in the operating room of Pariaman Hospital. In conclusion, there is a relationship between family support and spiritual needs of preoperative patients in the operating room of Pariaman Hospital. It is hoped that families will be able to provide support and facilitate spiritual needs to reduce the level of anxiety of preoperative patients